Improving family coping during the second trimester of pregnancy - Fajri Khoiriyah; Agustina Rahmawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The second trimester of pregnancy is a period of adaptation that requires families to prepare for physical, psychological, and social changes in pregnant women. Family readiness is very important in improving coping skills to support the health of mothers and pregnancies. Purpose: This final nursing thesis aims to describe family nursing care with readiness to improve family coping skills in the second trimester. Method: The method used was a case study with a family nursing process approach that included assessment, nursing diagnosis, planning, implementation, and evaluation. The nursing interventions provided were health education on the second trimester of pregnancy, demonstrations of pregnancy exercises, and efforts to improve family coping. Results: The results of nursing care showed an increase in family knowledge and an increase in family coping skills in dealing with the second trimester of pregnancy. Conclusion: The conclusion of this scientific paper is that family nursing care is effective in improving family coping skills during the second trimester of pregnancy and is expected to be a reference in the implementation of family nursing care for pregnant women and family members who are expected to always be actively involved in the care process.